The Ambiguities of an Ambiguity-Reading: A Critical Reading of The Function of Ambiguity in the Process of Reading - Parsa Janbeh Saraie (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As a communicative-epistemological concept, ambiguity is pivotal to any discussion of reading. Due to its roots in different fields of knowledge, as well as its dependence on age, genre, style, etc., ambiguity finds different embodiments in different circumstances. Therefore, it would be very difficult to discuss the concept without delimiting it to specific ages or genres. This paper is a meta-commentary on “The Function of Ambiguity in the Process of Reading Texts” by Forough Sahba. Via her analysis of some modernist and postmodernist narratives, Sahba has argued that despite the theory of the death of the author, modernist and postmodernist uses of ambiguity show the centrality of the author. The book is informative and especially helpful in defining different types of ambiguity. However, it has some shortcomings: it has no literature review; its classifications of ambiguity are not satisfying; and it has a few inconsistencies in its form and content. Moreover, it is based on a contradictory claim.